The Implementation of Good University Governance in State Universities - Rulyanti Susi Wardhani; Taufik Taufik; Luk luk Fuadah; Saadah Siddik (LPPM Universitas Terbuka, 2019)
This study aims to determine the differences in the implementation of good university governance at state universities in South Sumatra and Bangka Belitung. The state universities were Bangka Belitung University, Sriwijaya University, Sriwijaya State Polytechnic, and Bangka Belitung Manufacturing Polytechnic. The principles of good university governance in this study include governance structure, autonomy, accountability, leadership, and transparency. The respondents of the study were structural officials. Research data were collected using a questionnaire. The analysis used Friedman different test because the groups comprised new and long-established state universities. The results of the analysis indicate that accountability and transparency in the implementation of good university governance in Bangka Belitung University are different from those in Sriwijaya University. Meanwhile, the implementation of good university governance in Sriwijaya Polytechnic is similar to that in Bangka Belitung Manufacturing Polytechnic.